A retrospective study of the epidemiology, management and outcomes of patients with dialysis-requiring acute kidney injury, over a 24-month period, at Helen Joseph Hospital, Johannesburg, South Africa - Naidu, Yashika (University of the Witwatersrand, Johannesburg, 2024)
Background Dialysis-requiring acute kidney injury (AKI) carries significant morbidity and mortality. A cohort of patients was reviewed at Helen Joseph Hospital (HJH) to contribute to local knowledge on the epidemiology, referral patterns, and outcome of dialysis-requiring AKI. Methods A retrospective review was conducted of patients receiving dialysis for AKI at HJH between 1 January 2019 and 31 December 2020. Patient demographics and aetiologies of AKI were described. Effects of baseline characteristics and aetiology of AKI on patient survival, duration of hospitalisation, and renal function recovery were analysed using Cox proportional hazards modelling and binomial regression analyses. Results Dialysis-requiring AKI occurred in younger median age. Human immunodeficiency virus (HIV) infection (38.7%), hypertension (27.4%) and diabetes mellitus (12.3%) were common comorbidities. Community-acquired AKI predominated with significant renal dysfunction at presentation. Leading causes of AKI were sepsis (51.9%) and hypovolaemia (26.4%). Mortality was high (56.6%). Age and diabetes increased mortality and reduced renal recovery. Sepsis (HR 1.48, 95% CI 1.37–1.60, P < 0.001) and cardiorenal syndrome (CRS) type 1 (HR 1.78, 95% CI (1.57–2.01, P < 0.001) increased mortality. HIV infection did not increase the risk of mortality and showed an increased likelihood of renal recovery (OR 1.71, 95% CI 1.51–1.95, P < 0.001). Chronic kidney disease was prevalent in survivors. Conclusion Results resemble that of other low- and middle-income countries. People living with HIV may be at increased risk of dialysis-requiring AKI. AKI carries a high mortality rate. Sepsis and CRS carry an increased risk of death; sepsis-associated AKI and comorbid diabetes are associated with reduced odds of renal recovery to dialysis-free levels.
A research report submitted In fulfillment of the requirements for the degree of Master of Medicine to the Department of Clinical Medicine, Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg 2024
Keywords: Epidemiology; Acute kidney injury; Helen Joseph Hospital; UCTD; SDG-3: Good health and well-being